Impacts of Phyllanthus niruri extract on biomarker levels, macrophage count, and lesion area in an endometriotic rat model - Wulandari, Eka T.; Soetrisno, Soetrisno; Purwanto, Bambang; Reviono, Reviono; Wasita, Brian; Laqif, Abdurrahman (Narra J, 2024)
Endometriosis is a gynecological disorder characterized by chronic inflammation, anatomical changes, prolonged pain, and infertility. On the other hand, Phyllanthus niruri is recognized for its pharmacological effects, which might be beneficial in managing endometriosis. The aim of the study was to investigate the pharmacological effects of P. niruri as a potential therapy for endometriosis by using an animal model. An experimental laboratory study with randomized, controlled trial, pre-test, and post-test design using 40 female Wistar rats (Rattus norvegicus) was conducted at the Integrated Research and Testing Laboratory (LPPT) of Universitas Gadjah Mada, Yogyakarta, Indonesia, from February to June 2023. Endometriosis was induced in female Wistar rats by suturing a 0.5 cm2 flap from the uterine horn to the peritoneal cavity. Changes in serum interleukin 1β (IL-1β), malondialdehyde (MDA), and matrix metalloproteinase 9 (MMP-9), before and after the treatment, were analyzed using enzyme-linked immunosorbent assay. Hematoxylin and eosin (HE) staining were used to evaluate lesion size and macrophage quantity. The results suggested that the P. niruri extract with a dose of 196 mg/200 g body weight (BW) could significantly attenuate serum IL-1β (p=0.004), MMP-9 (p=0.021), and MDA (p=0.021). Rats receiving the P. niruri extract (196 mg/200 g BW) had significantly higher macrophage counts (p=0.003), but similar lesion area (p=0.093) as compared with the negative control. In conclusion, P. niruri demonstrated promising therapeutical effects on endometriosis by modulating IL-1β, MDA, and MMP-9 levels, although the effect was not pronounced on macrophage counts and lesion area.